Outsiderzy poszukujący sensu życia (Mury Hebronu, Biały kruk, Przez rzekę, Dziewięć, Taksim) - Kwolek, Justyna (Dydaktyka Polonistyczna, 2017)
In the adumbration titled Outsiders looking for the meaning of life, the author shall presentseveral groups of selected characters portrayed in the prose by Andrzej Stasiuk. Among the discussedgroups one finds prisoners described in Mury Hebronu, wanderers accounted for in Biały Kruk andTaksim, femme fatales portrayed in the storybook titled Przez rzekę, as well as tragic heroes illustratedin the novel Dziewięć. All these characters might be said to stay in some kind of relationship becausethey share the overwhelming feeling of alienation – either by choice or due to the rejection from thesociety – and they all struggle to find any deep meaning in human life in the senseless surroundingworld, but – unfortunately – the fail. The feeling of loneliness, alienation and the existential fear arethe features which might be used to portray all the characters of the aforementioned prose.